2012
DOI: 10.1590/s0100-879x2012007500168
|View full text |Cite
|
Sign up to set email alerts
|

The increased but non-predominant expression of Th17- and Th1-specific cytokines in Hashimoto’s thyroiditis but not in Graves’ disease

Abstract: Hashimoto's thyroiditis (HT) is considered to be mediated mainly by Th1 cells, but it is not known whether Graves' disease (GD) is associated with Th1 or Th2 predominance. Th17 cells, a novel subset of Th cells, play a crucial role in the pathogenesis of various autoimmune disorders. In the present study, the expression of IL-17A and IFN-γ was investigated in patients with HT or GD. mRNA expression of IL-17A and IFN-γ in peripheral blood mononuclear cells (PBMC) from 43 patients with autoimmune thyroid disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
57
0
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 26 publications
4
57
0
8
Order By: Relevance
“…Qin et al demonstrated increased expression of Th1-related cytokines in both the thyroid gland and PBMCs of HT patients. 30 Moreover, increased expression of Th1-related cytokines has been associated with elevated titres of anti-TPO antibodies, the destruction of thyroxisomes and the induction of apoptosis in thyroid follicular cells. [31][32][33] However, the importance of the role of Th2 cells in the pathogenesis of HT is still debatable.…”
Section: Discussionmentioning
confidence: 99%
“…Qin et al demonstrated increased expression of Th1-related cytokines in both the thyroid gland and PBMCs of HT patients. 30 Moreover, increased expression of Th1-related cytokines has been associated with elevated titres of anti-TPO antibodies, the destruction of thyroxisomes and the induction of apoptosis in thyroid follicular cells. [31][32][33] However, the importance of the role of Th2 cells in the pathogenesis of HT is still debatable.…”
Section: Discussionmentioning
confidence: 99%
“…Obviously, the influence of nicotine or other cigarette smoke compounds on the immune system is regulated by many factors, but cigarette smoke exposure is believed to inhibit Th1 cytokine production and may lead to enhancement of Th2 response [62]. Since Hashimoto's thyroiditis is regarded as a predominantly Th1 disease, the suppressive effect of cigarette smoking on Th1 response may explain the decreased risk of this disease among smokers [64,65]. The increase in risk of GD and GO in smokers may be caused by the Th2 cytokines involvement and enhancement of Th2 response, which is also considered as one of the main factors in pathogenesis of GD and GO.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several pathogens can shift the T cells balance toward a more immunosuppressive state, where Tregs might be induced. It may have therapeutic benefits for patients suffering from Th1/Th17-mediated autoimmune diseases (in particular, HT) (Phenekos et al, 2004;Qin et al, 2012). The last-named mechanism is triggered by ligands of pathogen-associated molecular patterns receptors expressed on/into antigenpresenting immune cells (Den Dunnen et al, 2010;Jeong and Lee, 2011;Kawai and Akira, 2009;Zeuthen et al, 2008).…”
Section: Microorganisms In Triggering/abrogation Of Autoimmune Diseasesmentioning
confidence: 99%
“…The data obtained in animal models show that the administration of S. cerevisiae cells induces interleukin 10 (IL-10), which steers the immune system towards a regulatory T cell response (Generoso et al, 2010;Martins et al, 2009). It may have therapeutic benefits for patients suffering from Th1/Th17-mediated autoimmune diseases (in particular, HT) (Phenekos et al, 2004;Qin et al, 2012). In turn, D. hansenii has been found to stimulate immune response in fish (Reyes-Becerril et al, 2012).…”
Section: Introductionmentioning
confidence: 99%